Qatar FIFA World Cup 2022 - Elias, Jaan; Mobarak, Mushfiq; Rosenthal, Jean (London : Yale School of Management, 2020)
The FIFA World Cup attracted the largest revenues and audiences of any sporting event other than the Olympics. Countries vied to host the men's football finals every four years, which showcased 32 national winners of regional playoffs. In December 2010, Qatar won the bid to host the 2022 finals. It was the first country in the Middle East and the smallest country ever to host the quadrennial event.Qatar was a small peninsula in the Persian Gulf, with a population of around 2.4 million and a land area of 4,416 square miles, smaller than Connecticut. Its extensive fields of oil and natural gas had brought great wealth to its citizens. Controversy had dogged Qatar's successful bid for the 2022 Games since it was announced. Many claimed that the procedure through which FIFA, the international governing body of the sport, granted Qatar the bid had been flawed.Construction of the venues for the competition brought additional negative attention. Reports alleged that the foreign-national workers who were building the stadiums, hotels, and infrastructure were being mistreated. Qatar had made changes to its labor laws, but could it monitor the construction companies doing the work? What of the energy needed to build and run the venues?
Orginally Published In Elias, J., Rosenthal, J., & Mobarak, M. (2020). Qatar FIFA World Cup 2022. 20-013. New Haven, CT: Yale School of Management, Yale University.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Fédération internationale de football association -- Case studies; Soccer -- Corrupt practices -- Case studies